Warming and cooling device using thermoelectric Peltier elements tested on male mice. (October 2020) - Madrahimov, Nodir; Natanov, Ruslan; Khalikov, Abdurasul; Boyle, Erin C; Jonigk, Danny; Knoefel, Ann-Katrin; Siemeni, Thierry; Haverich, Axel
Hypothermia is a treatment strategy for different clinical conditions and an essential part of cardiopulmonary bypass in complex cardiac procedures. Clinically, cooling patients is achieved via a mattress and heat exchanger integrated into a membrane oxygenator connected to a waterbed using a refrigerator system based on volatile and toxic liquids. Peltier elements are known as environmentally friendly thermoelectric generators that enable rapid warming and cooling. In this paper, we describe the construction of a novel device for rapid and precise control of mouse warming and cooling using thermoelectric Peltier elements. Six male BALB/c mice were subjected to deep hypothermia and were rewarmed under full physiological monitoring. After rewarming, all animals were observed for two hours, and pathology was evaluated in several organs. All animals tolerated the rapid cooling process well and remained active after rewarming. Temperature-relevant changes were seen via electrocardiography, with heart-rate patterns showing a strong linear correlation to body temperature. No myocardial ischaemia was seen. However, two animals experienced bradycardic atrial fibrillation which spontaneously converted to normal sinus rhythm during rewarming. No histological damage was seen in the heart, liver, kidney or lungs. Our device can effectively be used for heat shock and hypothermia studies in mice, and we foresee no obstacles for its application to other small rodents such as hamsters and young rats. In comparison to known experimental and clinical methods of hypothermia, our device is environmentally friendly, cost-effective and easy to handle, allowing precise control and maintenance of body temperatures ranging from 18℃ to 42℃.